Risk of Hepatitis A in Dutch Hemophilia Patients - Mauser-Bunschoten, E P; Zaaijer, H L; van Drimmelen, A A J; Berg, H M van den; Roosendaal, G; Lelie, P N (Thrombosis and Haemostasis, 1995)
Recently, clotting factor preparations transmitted hepatitis A virus (HAV) to hemophilia patients. To study the risk of HAV infection in Dutch hemophilia patients, serum samples of 341 patients with hemophilia were tested for HAV antibodies (anti-HAV).197/341 patients (group 1) were treated with clotting factor concentrates produced from large plasma pools, 144/341 patients (group 2) were treated with small pool cryoprecipitate. The test results were compared to those of healthy blood donors (n = 19,746) of the same age. In addition stored serum samples (1983-1994) from hemophilia patients were tested for HAV antibodies.No increased risk of HAV infection was found in Dutch hemophilia patients. The anti-HAV prevalence in group 1 was 20%, in group 213% and in blood donors 41%. A significantly (p <0.002) lower percentage of HAV antibodies was found in hemophilia patients born in the 1950s using cryoprecipitate (11%) as compared to blood donors of the same age (40%), probably caused by passive administration of anti-HAV through clotting product. Passive immunization in the past was significantly (p <0.02) more often found in group 2 (41.7%) than in group 1 (28%).In the period 1983 till 1988 five seroconversions were seen in group 1 (2%) and one in group 2 (0.7%). Anti-HAV seroconversions were not observed after 1988.In a risk analysis we estimated that 2 plasma pools of 10,000 Dutch blood donors per year may contain HAV. The absence of HAV among Dutch hemophilia patients suggests that this contamination is successfully inactivated.